Improving farm-to-market linkages through contract farming: A case study of smallholder dairying in India - Birthal, Pratap Singh; Jha, Awadhesh K.; Tiongco, Marites; Narrod, Clare (International Food Policy Research Institute, 2008)
Contract farming is emerging as an important form of vertical coordination in the agrifood supply chain in India, and its socioeconomic consequences are attracting considerable attention in public policy debates. This study is an empirical assessment of the costs and benefits of contract farming in milk using information generated through field surveys in the western state of Rajasthan. Contract farming is found to be more profitable than independent production. Its major benefits come from a reduction in marketing and transaction costs, which are otherwise much higher in the open markets. Contract farming also contributes toward improving milk yield and reducing production costs, albeit not significantly. Dairy producers also benefit from provision of services and technical advice by integrators/firms who secure milk supplies from farmers through contract. The benefits of contract farming vary by scale of operation. Economies of scale are also important determinants of competitiveness, in which large farms (both contract and independent) have lower per unit cost due to buying of inputs in bulk and greater access to markets. Smallholders, on the other hand, derive significant benefits from a reduction in marketing and transaction costs due to their participation in contract farming.--Authors' Abstract